NUTRITIONAL STATUS ASSESSMENT OF PATIENTS IN A GENERAL PRACTITIONER'S OFFICE - Radka Kozáková; Lada Hrbáčová; Renáta Zeleníková (University of Ostrava, 2017)
Aim: The study aimed at determining the nutritional status of senior citizens in a general practitioner's office. Design: A cross-sectional study. Methods: Nutritional status was assessed with the Mini Nutritional Assessment (MNA), Malnutrition Universal Screening Tool (MUST), Mini Nutritional Assessment - Short Form (MNA-SF) and laboratory parameters (prealbumin, transferrin and CRP). The study comprised 241 participants. The significance of differences in selected nutritional markers for various groups was determined using a chi-squared test, Spearman's correlation coefficient and Fisher's test at a critical statistical significance level of 0.05. Results: Malnutrition was detected in a relatively high proportion of the elderly, ranging from 13% to 90% depending on the tools used. There were significant differences between the tools when identifying patients as malnourished or being at risk of malnutrition. The MNA revealed more patients at risk of or with malnutrition (90%) than the MNA-SF (58%) or MUST (13%). No statistically significant correlations were found either between nutritional status and biochemical markers of nutrition or between nutritional status and age of the elderly. Conclusion: In the general practice setting, nutrition of the elderly must not be neglected as adequate nutrition is a prerequisite for faster convalescence and return to a normal life. Keywords: assessment, biochemical markers, Malnutrition Universal Screening Tool (MUST), Mini Nutritional Assessment (MNA), Mini Nutritional Assessment - Short Form (MNA-SF), nutrition, patients over 65 years of age.